Current and future climatic of species of the genus Pinus of Michoacan, Mexico - Manzanilla Quiñones, Ulises; Delgado-Valerio, Patricia; Martínez-Sifuentes, Aldo Rafael; Molina-Sánchez, Agustín (Ecosistemas y Recursos Agropecuarios, 2025)
Climate change scenarios are projections of future climate and evaluate how these modifications have an effect on the composition, structure and distribution of global biodiversity. The objective of this study was to test the hypothesis that climate change projections foresee a substantial reduction in the climatic habitat of 14 species of the genus Pinus in Michoacán, Mexico. Geographic records were obtained for 14 pine species distributed in Michoacán. The 19 current (1970-2000) and future (2041-2060) bioclimatic variables were downloaded from the Global Circulation Models (GCMs) HADGEM3_ES and MPI_ESM_LR with a shared socioeconomic trajectory 245 from WORLDCLIM. The records and variables were loaded into Maxent, where 75% of the records were used to train and 25% to validate the models, which were evaluated using the area under the curve (AUC), partial Roc and Z tests. The results of these tests were excellent (AUC > 0.88, > 1.52, p < 0.01). The most relevant variables for the 14 species were average maximum temperature of the warmest period (Bio5), precipitation of the warmest quarter (Bio18), accumulated annual precipitation (Bio12) and average minimum temperature of the coldest period (Bio6). Based on the results obtained, the hypothesis is accepted, because significant reductions in climatic habitat are expected for 13 of the 14 species, with the species most susceptible to climate change being P. hartwegii, with a reduction in climatic habitat of 42.3%, P. leiophylla (43.5%), P. devoniana (44.2%), P. herrerae (59.7%) and P. martinezii (62.9%).
Keywords: Spatial analysis; Potential distribution; Climate change scenarios; Models of circulation global; Climate niche